2017
DOI: 10.3758/s13423-017-1246-3
|View full text |Cite
|
Sign up to set email alerts
|

Right away: A late, right-lateralized category effect complements an early, left-lateralized category effect in visual search

Abstract: According to the Sapir-Whorf hypothesis, learned semantic categories can influence early perceptual processes. A central finding in support of this view is the lateralized category effect-namely, the finding that categorically different colors (e.g., blue and green hues) can be discriminated faster than colors within the same color category (e.g., different hues of green), especially when they are presented in the right visual field. Because the right visual field projects to the left hemisphere, this finding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
1
6
1
Order By: Relevance
“…In RTs, there was no interaction of category and visual field, suggesting that the visual discrimination benefit was not stronger in (or exclusive to) targets in the RVF, in contrast with some previous findings (Drivonikou et al, 2007;Franklin et al, 2008;Gilbert, et al 2006;Roberson, Pak, & Hanley, 2008;Zhou et al, 2010) but in line with others (Witzel & Gegenfurtner, 2011, 2015, 2016. Roberson et al (2008) found lateralization of CP to the RVF only in fast responders (Constable & Becker, 2017). However, Bfastr eactions in previous studies were still relatively slow compared with the present study, suggesting that the visual search task used here was generally easier and more susceptible to bottom-up visual pop-out, and the average category-advantage was small compared to other studies.…”
Section: Lateralization Of Categorical Perceptioncontrasting
confidence: 70%
See 3 more Smart Citations
“…In RTs, there was no interaction of category and visual field, suggesting that the visual discrimination benefit was not stronger in (or exclusive to) targets in the RVF, in contrast with some previous findings (Drivonikou et al, 2007;Franklin et al, 2008;Gilbert, et al 2006;Roberson, Pak, & Hanley, 2008;Zhou et al, 2010) but in line with others (Witzel & Gegenfurtner, 2011, 2015, 2016. Roberson et al (2008) found lateralization of CP to the RVF only in fast responders (Constable & Becker, 2017). However, Bfastr eactions in previous studies were still relatively slow compared with the present study, suggesting that the visual search task used here was generally easier and more susceptible to bottom-up visual pop-out, and the average category-advantage was small compared to other studies.…”
Section: Lateralization Of Categorical Perceptioncontrasting
confidence: 70%
“…Furthermore, CP is possible as soon as we acquire linguistic or semantic knowledge that allows forming conceptual stimulus categories. Whether this is also reflected in behavioral measures, such as RTs depends, in our opinion, on task difficulty (Constable & Becker, 2017;Regier & Xu, 2017). In line with a hierarchical predictive processing account of perception, linguistic category information may inform perceptual predictions and directly enhance perception (Clark, 2013;Friston, 2009;Lupyan & Clark, 2015), especially in difficult tasks with high perceptual uncertainty (Regier & Xu, 2017).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…There is some evidence that lateralized categorization may be produced independent of linguistic categories, suggesting that the lateralization is due to differences in attention to the visual fields (Alvarez, Clifford, Holmes, & Franklin, 2012). Others have argued that the lateralization of category effects depends on the time course of perceptual processing Constable & Becker 2017). Nevertheless, it remains an open question why lateralisation was found in some but not in other studies.…”
Section: Open Questionsmentioning
confidence: 91%